Estimativa de parâmetros hidráulicos do solo utilizando tensiometria com alguns sistemas de leitura - Freire, Alcione Guimarães (2016)
Soil solution drainage is monitored by means of instruments able to measure the potential energy of the solution due to the forces of the soil matrix adhesion. Therefore, the tensiometer has emerged as an excellent tool for directly measuring the water energy in the soil and allowing in situ measurements. The objective of this research was to determine the equilibrium time after needle insertion when using the tensiometer with digital tensimeter, measure two systems alternative to the mercury manometer for the measurement of soil water matric potential and check its implications on the estimates of soil moisture, soil water flux density and hydraulic conductivity as a function of moisture. Moreover, the objective was to compare the soil hydraulic parameters obtained by inverse modeling using the Hydrus-1D model, from the matrix potentials for each reading system. The experiment was conducted in the same arrangement to determine the hydraulic conductivity through the instantaneous hydraulic profile method. Tensiometers were installed at depths of 0.20, 0.35 and 0.50 m for each reading system, with six replicates. Data were analyzed using tests of coefficients of the line and statistical indices, considering the Hg manometer as the standard method. It follows that the reading of the tensiometer with digital tensimeter must be performed within 30 seconds after needle insertion in the tube; the Bourdon gauge can replace the Hg manometer in the measurement of the soil water matric potential in the moisture range from saturation to field capacity; alternative systems lead to underestimation of the flux density and hydraulic conductivity as a function of moisture and overestimation of the hydraulic gradient; therefore, they are not suitable for the estimation of these hydraulic parameters; the tensiometer reading systems converge in the estimation of hydraulic parameters by inverse modeling.